Les chartes originales de l’abbaye de Jumièges jusqu’en 1120 - Benoît-Michel Tock (Tabularia)
The archives of Jumièges abbey are one of the richest in 11th cent. Normandy. Most of the charters of Jumièges are preserved as originals. Thanks to a new database of the original charters prior to 1121 preserved in France, it is possible to study these charters and their connections to other French charters. Many of the Jumièges charters have same formulas, and this proofs that they were drafted by the monks of Jumièges. But there is a great formal diversity. The only validation of those charters is the subscription, which is not autograph, with the exception of the subscription crosses. Generaly speaking, Jumièges is master of its own diplomatics; the influence of Tours and Marmoutier isn’t overwhelming.